2010
DOI: 10.1111/j.1365-2222.2010.03508.x
|View full text |Cite
|
Sign up to set email alerts
|

Lipocalin2 protects against airway inflammation and hyperresponsiveness in a murine model of allergic airway disease

Abstract: These data indicate a protective role for Lcn2 in allergic airway disease, suggesting a pro-apoptotic effect as the underlying mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 28 publications
1
21
0
1
Order By: Relevance
“…Lcn2, which is a small protein of 25 kD, is a transporter with several functions, including regulation of immune responses, cell growth and differentiation, transportation of iron, and synthesis of prostaglandin (Flower et al, 2000;Grzyb et al, 2006). Recent studies have shown that Lcn2 is up-regulated following allergen sensitization and airway challenges in lung tissues and have protective functions in allergic airway disease (Dittrich et al, 2010). Serpina3n is a member of a multigene family of serpins, which are the largest family of protease inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Lcn2, which is a small protein of 25 kD, is a transporter with several functions, including regulation of immune responses, cell growth and differentiation, transportation of iron, and synthesis of prostaglandin (Flower et al, 2000;Grzyb et al, 2006). Recent studies have shown that Lcn2 is up-regulated following allergen sensitization and airway challenges in lung tissues and have protective functions in allergic airway disease (Dittrich et al, 2010). Serpina3n is a member of a multigene family of serpins, which are the largest family of protease inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…ITIH1 was reported previously to possess anti-inflammatory activity through the inhibition of complement proteins (30). Lipocalin-2, a molecule involved in antimicrobial defense (28), protects against airway inflammation in a mouse model of allergic asthma (23). In addition, the tumor necrosis factor receptor superfamily 9 protein (Tnfrsf9) was shown previously to push the balance between Th17 cells and Tregs in favor of Treg generation (40).…”
Section: Resultsmentioning
confidence: 99%
“…Other studies revealed that Lcn2 also binds other types of siderophores, such as bacillibactin ( B. anthracis ) (157) and carboxy-mycobactin (mycobacteria) (158). Lcn2 is one of the most commonly studied novel biomarkers (159) and has emerged as a promising biomarker for different pulmonary diseases (97), kidney injury (160163), liver failure (164), and tumorigenesis (144). Thus, the clinical relevance of Lcns is rapidly increasing even though the exact mechanisms behind their functions remain to be elucidated.…”
Section: Antimicrobial Peptidesmentioning
confidence: 99%